2008
DOI: 10.1007/s10803-008-0621-3
|View full text |Cite
|
Sign up to set email alerts
|

Autism symptoms in Attention-Deficit/Hyperactivity Disorder: A Familial trait which Correlates with Conduct, Oppositional Defiant, Language and Motor Disorders

Abstract: It is hypothesised that autism symptoms are present in Attention-Deficit/Hyperactivity Disorder (ADHD), are familial and index subtypes of ADHD. Autism symptoms were compared in 821 ADHD probands, 1050 siblings and 149 controls. Shared familiality of autism symptoms and ADHD was calculated using DeFriesFulker analysis. Autism symptoms were higher in probands than siblings or controls, and higher in male siblings than male controls. Autism symptoms were familial, partly shared with familiality of ADHD in males.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
133
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 202 publications
(159 citation statements)
references
References 52 publications
15
133
4
Order By: Relevance
“…Additional details about the clinical characteristics and the diagnostic process of this sample have been described earlier (Brookes et al 2006;Kuntsi et al 2006;Chen et al 2008;Christiansen et al 2008;Zhou et al 2008;Mulligan et al 2009). Briefly, co-occurring disorders were the following:.…”
Section: Participantsmentioning
confidence: 99%
“…Additional details about the clinical characteristics and the diagnostic process of this sample have been described earlier (Brookes et al 2006;Kuntsi et al 2006;Chen et al 2008;Christiansen et al 2008;Zhou et al 2008;Mulligan et al 2009). Briefly, co-occurring disorders were the following:.…”
Section: Participantsmentioning
confidence: 99%
“…Nijmeijer et al (2009) reported that ADHD and traits of ASD were genetically independent of one another. Conversely, Mulligan et al (2009) reported that 56 % of the phenotypic correlation between ADHD and ASD could be attributed to shared familial influences.…”
Section: Introductionmentioning
confidence: 99%
“…Twin, family, and linkage studies indicate that attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorders (ASDs) share a portion of their heritable etiology (1)(2)(3)(4)(5)(6). Genome-wide association studies found rare copy number variants that were shared between the two disorders (7).…”
Section: Introductionmentioning
confidence: 99%